UNFSS Science Days Side Event: Reforming Agricultural Policies to Support Food Systems Transformation - Gulati, Ashok (2021)
Ashok Gulati POLICY SEMINAR UNFSS Science Days Side Event: Reforming Agricultural Policies to Support Food Systems Transformation Co-organized by IFPRI, Indian Council for International Economic Research (ICRIER) and Academy of Global Food Economics and Policy, China Agricultural University JUL 7, 2021 - 09:30 AM TO 11:00 AM EDT